2013
DOI: 10.15560/9.6.1519
|View full text |Cite
|
Sign up to set email alerts
|

Amphibia, Anura, Hylidae, Sphaenorhynchus prasinus Bokermann, 1973: First record of the genus and species for the State of Alagoas, Brazil

Abstract: The genus Sphaenorhynchus Tschudi, 1838 can be characterized by the following morphological synapomorphies: posterior ramus of pterygoid absent; zygomatic ramus of squamosal absent or reduced to small knob; pars facialis of maxilla and alary process of premaxilla reduced; postorbital process of maxilla reduced, not in contact with quadratojugal; neopalatine reduced to sliver or absent; pars externi plectri entering tympanic ring posteriorly; pars externa plectri round; hyale curved medially; coracoids and clav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…canga (see Araujo‐Vieira et al, 2015 ), S . prasinus (see da Silva et al, 2013 ), S . pauloalvini (see Freitas et al, 2009 ), and S .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…canga (see Araujo‐Vieira et al, 2015 ), S . prasinus (see da Silva et al, 2013 ), S . pauloalvini (see Freitas et al, 2009 ), and S .…”
Section: Discussionmentioning
confidence: 99%
“…Biogeography of the genus Gabohyla (G. pauloalvini (Bokermann, 1973)) together with 11 other species of the genus Sphaenorhynchus (S. botocudo Caramaschi et al, 2009, S. bromelicola Bokermann, 1966, S. cammaeus Roberto et al, 2017, S. canga Araujo-Vieira et al, 2015, S. caramaschii Toledo et al, 2007, S. mirim Caramaschi et al, 2009, S. palustris Bokermann, 1966, S. planicola (Lutz & Lutz, 1938, S. platycephalus (Werner, 1894), S. prasinus Bokermann, 1973, and S. surdus (Cochran, 1953)), occur in the Atlantic Forest, from the State of Pernambuco to the State of Rio Grande do Sul (Araújo-Vieira et al, 2015Bokermann, 1966Bokermann, , 1973Caramaschi et al, 2009;Cochran, 1953;da Silva et al, 2013;de Freitas et al, 2009;Lacerda & Moura, 2013;Lutz & Lutz, 1938;Melo et al, 2018;Roberto et al, 2017;Toledo et al, 2007;Werner, 1894), while the other three species have distribution associated with the Amazonia and the Orinoco basin (S. carneus (Cope, 1868), S. dorisae (Goin, 1957), and S. lacteus (Daudin, 1800)) (Benício et al, 2011;La Marca et al, 2008). Sphaenorhynchini monophyly has always been supported (Araujo-Vieira et al, 2020;Duellman et al, 2016;Pyron, 2014) and several morphological synapomorphies have been suggested…”
Section: T a X O N O M Y C L A S S I F I C A T I O Nmentioning
confidence: 99%
See 2 more Smart Citations